Systematical assessment of digit ratio in a female masculinization disease: polycystic ovary syndrome - Yan, Xueqi; Zhu, Aiqing; Li, Yexing; Yang, Ziyi; Wang, Yuteng; Liu, Li; Liu, Wei; Liu, Dan; Li, Fenghua; Du, Juan; Cheng, Fang; Gao, Xueying; et al. (Frontiers in Endocrinology, 2023)
Background: In recent years, the right ratio of 2nd and 4th digit length (2D:4D) is regarded as an anatomical marker of prenatal testosterone exposure. Polycystic ovary syndrome (PCOS) is a female masculinized disease and is determined by prenatal testosterone exposure. Whether the ratio in the right hand of PCOS women is reduced compared with the non-PCOS or not is under debate. To further investigate the relationship between PCOS and digit ratio, we systematically measured all the digit ratio. Methods: we recruited 31 non-PCOS women, 116 PCOS women and 40 men and systematically measured all the ratio of digit length (2D:3D, 2D:4D, 2D:5D, 3D:4D, 3D:5D, 4D:5D) of right hands and left hands. Results: Significantly lower digit ratio (P=0.033 in left 2D:3D and P=0.033 in left 2D:4D) was observed in PCOS compared with non-PCOS women. In the subgroup analysis, the left ratio of digit length in 2D:3D and 2D:5D of hyperandrogenism subgroup was lower than non-hyperandrogenism subgroup without statistical significance. Logistic regression model of PCOS revealed that 2D:3D, 2D:4D, 2D:5D and 3D:4D of left hands were statistically related to diagnosis of PCOS among all the digit ratios. Conclusion: not only 2D:4D but also other digit ratios, such as 2D:3D and 2D:5D represented the marker of prenatal testosterone exposure and may be anatomical marker of PCOS. Digit ratio in left hand was more stable than in right hand due to long-time use resulting in distortion.